A stable spin-structure found in a 3-body system with spin-3 cold atoms and its role in N-body condensates - Y. M. Liu (Nature Portfolio, 2021)
Abstract We have found a stable spin-structure of N $$=$$ = 3 system in which three spin-3 atoms are trapped and coupled to total spin S $$=$$ = 3. We have proved that a pair of this structure is nearly an exact solution for N $$=$$ = 6 systems in a very broad district in the parameter-space. Comparing with the well-known singlet pairs, this pair is a more promising candidate to serve as a building block for large N systems with spin-3 atoms. This is because the spin-structure of the latter can be modified depending on the interactions to reduce the energy while the singlet pairs can not. In fact, we have proved that, for a specific set of strengths (a point in the parameter-space) the product state based on this pair is an exact solution of the N-body Hamiltonian. Thus, in the neighborhood of this point, the product state will appear as an approximate solution. However, how broad this neighborhood would be remains to be clarified.